Effects of dietary raffinose on growth, non-specific immunity, intestinal morphology and microbiome of juvenile hybrid sturgeon (Acipenser baeri Brandt ♀ × A. schrenckii Brandt ♂). Issue 72 (January 2018) - Xu, Guanling; Xing, Wei; Li, Tieliang; Ma, Zhihong; Liu, Caixia; Jiang, Na; Luo, Lin
Abstract: This study was performed to determine the efficacy of raffinose on the growth, non-specific immunity, intestinal morphology and microbiota of juvenile hybrid sturgeon, ( Acipenser baeri Brandt ♀ × A . schrenckii Brandt ♂). Hybrid sturgeons were divided into 2 groups and each group was fed with diets supplemented with or without raffinose for 56 days. Hybrid sturgeon fed diet supplemented with raffinose had significantly higher final body weight (FBW), specific growth rate (SGR), and weight gain ratio (WGR) than fish fed the control diet ( P < 0.05). Raffinose in diet had no negative effect on feed intake (FI) and feed conversion ratio (FCR) ( P > 0.05). Compared with the control diet, the myeloperoxidase (MPO) and respiratory burst (NBT) activitives were significantly higher in sturgeon fed the raffinose supplemented diet ( P < 0.05). The increasing of intestinal villi area and mucosal folds were observed in intestinal tract of sturgeon when they fed the raffinose supplemented diet. Meanwhile, the residual bait of intestinal tract was relatively lower in sturgeon with raffinose treatment. High-throughput sequencing revealed that majority of reads derived from the sturgeon digesta were constituted by members of Proteobacteria, Firmicutes, Fusobacteria and Actinobacteria. Shannon's diversity index existed significant difference among dietary treatments indicating that the overall microbial community was modified to a large extent by dietary raffinose. In conclusion, supplementation of the diet with raffinose is capable of improving hybrid sturgeon growth performances and intestinal morphology, modifying the intestinal microbial composition. Highlights: Sturgeon fed diet supplemented with raffinose had significantly improved growth performance. The myeloperoxidase and respiratory burst activitives were increased in sturgeon fed the raffinose supplemented diet. Supplementation of hybrid sturgeon diets with raffinose is capable of changing intestinal histology. The overall microbial community of sturgeon was modified to a large extent by dietary raffinose.